Penerapan Terapi Dzikir Asmaul Husna Terapi Parameter Hemodinamik Non Invasif Pasien Kritis di Ruang HCU Anggrek 2 RSUD Dr Moewardi - Nur Rohmanni Yuliana; Bagas Biyanzah Drajad Pamukhti; Isti Wulandari (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Critically ill patients are individuals with unstable health conditions who require close monitoring of hemodynamic parameters. The high mortality rate among critically ill patients treated in intensive care units reaches 36.5% of 33,148 patients. Hemodynamic instability in critically ill patients can be influenced by underlying diseases, medical interventions, as well as physical and psychological stress responses during treatment. Therefore, in addition to pharmacological therapy, non-pharmacological interventions such as Asmaul Husna dhikr therapy are needed, as they can provide a relaxation effect and help stabilize hemodynamic parameters in critically ill patients. To determine the outcomes of the implementation of Asmaul Husna dhikr therapy. This study used a descriptive case study method involving two critically ill patients with unstable non-invasive hemodynamic parameters. Changes in non-invasive hemodynamic parameters were observed in both respondents after the implementation of Asmaul Husna dhikr therapy. In respondent 1, the hemodynamic status was initially categorized as increased and became stable after the intervention. Similarly, in respondent 2, the hemodynamic status changed from increased before the intervention to stable after the intervention. The implementation of Asmaul Husna dhikr therapy can be used as a complementary therapy to help stabilize hemodynamic parameters in critically ill patients.